Organizational Change Strategies within Healthcare. Issue 3 (October 2013) - Steinke, Claudia; Dastmalchian, Ali; Blyton, Paul; Hasselback, Paul
This study explores ways in which healthcare organizations can improve their organizational fitness for change using Beer and Nohria's framework of Theory E (concentrating on the economic value of change) and Theory O (concentrating on the organization's long-term capabilities for change). Data were collected from senior leaders/medical directors from health regions in Alberta. The results show that even though there is a tendency for reliance on Theory E change strategies, the respondents demonstrated other preferred approaches to change.